2018
DOI: 10.1002/2017gl076357
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Processing Lowers the Ice Nucleation Activity of Birch and Alder Pollen

Abstract: Pollen carry water extractable compounds with ice nucleating (IN) activity. This study investigates whether the hydroxyl radical, as the major atmospheric oxidant, can affect the IN activity of silver birch and grey alder subpollen particles under in‐cloud conditions for deposition freezing mode conditions at 234 K. It is found that oxidation increases the supersaturation ratio with respect to ice necessary for the onset of ice nucleation and decreases the fraction of particles which initiate ice nucleation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In fact, atmospheric photochemical processing of organic aerosols has been shown to increase CCN ability (Slade et al, 2017;Wong et al, 2011). However, the effect of photochemical processing of organic matter on ice nucleation is unknown, although recent work on pollen in deposition freezing mode suggests a decrease in ice activity (Gute and Abbatt, 2018). Our study links a photochemical mechanism with CCN and with INP efficiencies applicable for an atmospheric organic aerosol.…”
Section: Introductionmentioning
confidence: 64%
“…In fact, atmospheric photochemical processing of organic aerosols has been shown to increase CCN ability (Slade et al, 2017;Wong et al, 2011). However, the effect of photochemical processing of organic matter on ice nucleation is unknown, although recent work on pollen in deposition freezing mode suggests a decrease in ice activity (Gute and Abbatt, 2018). Our study links a photochemical mechanism with CCN and with INP efficiencies applicable for an atmospheric organic aerosol.…”
Section: Introductionmentioning
confidence: 64%
“…Amato et al (2015) show that typical IN active bacteria retain their activity on time scales characteristic for the transport between the source and the cloud. Gute and Abbatt (2018) report no effect on IN activity due to UV or sunlight exposure; however, for deposition freezing mode they found that chemical in-cloud oxidation lowers the IN activity of pollen but not of mineral dust.…”
Section: Atmospheric and Postdepositional Alteration Of Inpmentioning
confidence: 92%
“…The geographical dispersion of anemophilous plants largely relies on pollen dispersal, which in turn depends on the emission, transport and deposition of pollen grains; therefore, pollen plays a key role in the evolution of many ecosystems (Womack et al, 2010;Fröhlich-Nowoisky et al, 2016). In addition, PBAPs can serve as giant cloud condensation nuclei (CCN) and ice nucleating particles (INPs), significantly impacting the formation and properties of clouds and thus radiative balance and precipitation (Möhler et al, 2007;Ariya et al, 2009;Pratt et al, 2009;Pope, 2010;Pummer et al, 2012; Gute and Abbatt, 2018). It has also been proposed that PBAPs may have significant impacts on chemical composition of aerosol particles via heterogeneous and multiphase chemistry (Deguillaume et al, 2008;Estillore et al, 2016;Reinmuth-Selzle et al, 2017;Shiraiwa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%